Response of Holstein steers fed a soybean hull-based diet to amino acid supplementation when the methionine requirement was met - Lambert, B.D.; Löest, C.A.; Titgemeyer, Evan C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A study was conducted to determine the response to amino acid supplementation when the first limiting amino acid (methionine) was provided in excess. Three ruminally cannulated Holstein steer calves (281 lb) were fed 4.8 lb of a soybean hullbased diet (87% soyhulls and 8% wheat straw) daily. Methionine is the first limiting amino acid on diets of this type, and all steers were abomasally infused with 10 g/day of methionine to ensure that this requirement was met. Treatments consisted of increasing amounts (100, 250, or 400 g/day) of an amino acid mixture supplied abomasally. Calves received decreasing amounts of supplemental energy in the form of volatile fatty acids and dextrose as amino acid infusion increased in order for treatments to remain isoenergetic. Nitrogen balance increased as amino acid supply increased, indicating that amino acids other than methionine limited protein deposition. The nitrogen balance change between the 100 and 250 g/day amino acid treatments was greater than that from 250 to 400 g/d, suggesting that 250 g/day supplied amounts of amino acids near the requirement.
Keywords: Beef; Amino acids; Requirements; Steers